Graphene oxide coated quartz sand as a high performance adsorption material in the application of water treatment. Issue 11 (7th February 2015) - Hou, Wenjun; Zhang, Yimei; Liu, Tong; Lu, Hongwei; He, Li
<x xml:space="preserve">Abstract</x> GO firmly planted on the surface of quartz sand, will not fall off and cause secondary pollution. A series of experiments show that the GO coated sand (GOS) granules have a strong adsorption performance for organic matter and heavy metal ions.